1994
DOI: 10.1177/019262339402200402
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Diagrams: A Tool for Recording the Distribution of Nasal Lesions in Rats and Mice

Abstract: Knowledge of patterns of lesion distribution can provide insight into the relative roles played by regional tissue dose and local tissue susceptibility in toxic responses to xenobiotics in the nose and assist assessment of potential human risk. A consistent approach is needed for recording lesion distribution patterns in the complex nasal airways of rats and mice. The present work provides a series of diagrams of the nasal passages of the Fischer-344 rat and B6C3F1 mouse, designed for mapping nasal lesions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(136 citation statements)
references
References 29 publications
2
133
0
1
Order By: Relevance
“…Importantly under the conditions used, no EGFP-positive cells could be detected in the respiratory epithelium of the nasal cavity (data not shown). Panels (e-h) in Figure 4 demonstrate differences in morphology between regions in the nose consisting mostly of olfactory epithelium (e and f) and regions that contain respiratory epithelium (g and h) (also refer to Mery et al 30 ). …”
Section: Identification Of Cells Transduced By Raav5/5 In Nasal Epithmentioning
confidence: 95%
“…Importantly under the conditions used, no EGFP-positive cells could be detected in the respiratory epithelium of the nasal cavity (data not shown). Panels (e-h) in Figure 4 demonstrate differences in morphology between regions in the nose consisting mostly of olfactory epithelium (e and f) and regions that contain respiratory epithelium (g and h) (also refer to Mery et al 30 ). …”
Section: Identification Of Cells Transduced By Raav5/5 In Nasal Epithmentioning
confidence: 95%
“…The nasal epithelium (squamous, transitional, respiratory, and olfactory epithelium) and surrounding tissues, the vomeronasal organ and the trigeminal nerve were histologically examined for all animals. The nomenclature of the ethmoturbinates was partitioned according to the classification of the previous report (Mery et al, 1994). Histological findings were classified to the following degrees: mild, sporadic distribution and not detected at low magnification; moderate, easily found at low magnification.…”
Section: Experimental Design For Morphologymentioning
confidence: 99%
“…The nasal epithelium is an especially important target tissue for inhalation toxicity (Morgan and Harkema, 1996). However, systemic administration of xenobiotics could exert toxicity on the olfactory epithelium (Mery et al, 1994), and axotomy or bulbectomy has been reported to induce apoptosis of the olfactory sensory cells by interruption of axonal transport (Schwartz et al, 1991;Takeda, 1991, Suzuki et al, 1996). Apoptosis in various tissues caused by antimicrotubule agents including VCR, vinblastine sulfate (VBL), vindesine sulfate (VDS), and paclitaxel (PTX) is a very complex process associated with many protein kinase signaling pathway, and it is supposed that phosphorylation of bcl-2 and elevations of p53 and p21 lead to apoptosis (Wang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…14,20 Finally, the lower levels of gene expression we observe on the nasal septum compared to the lateral ciliated regions are consistent with the differences in fluid retention in these two regions. The ability to observe where the dose is retained, or the tissue-type targeted, 21 should be useful in the testing of pharmaceuticals, infectious agents, allergens and other gene vectors in these different epithelial tissues. The visualization of partial dose delivery distributions also suggests that whenever incomplete or inconsistent dosing (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The unilateral nasal airway gene expression produced when using these protocols 2,4 is consistent with this notion since we only observe patterns of gene expression in areas reached by the 4 µl dose, despite demonstrating the wide reach of the 20 µl (surrogate vector) dose throughout the entire nasopharynx. The nasopharynx epithelium is entirely ciliated respiratory epithelium 21 and it follows that if the nasopharynx could be effectively pre-treated around its full circumference with LPC, then homogeneous gene transduction might be achieved there. This novel lung airway-like site could potentially be used for modeling the effects of gene vectors or drugs on ciliated airway function within a tubular lung-like conducting airway, an option identified by others in related studies of mouse nasal electrophysiological function.…”
Section: Discussionmentioning
confidence: 99%